Results of a Retrospective Fracture Register of Distal Radius Fractures Built Up Using PROM - Rammensee, Johannes; von Matthey, Francesca; Biberthaler, Peter; Abel, Helen (Frontiers in Surgery, 2022)
Introduction: Although distal radius fractures (DRFs) are the most common fractures of the human body, the best treatment for every fracture type is still debatable. However, randomized controlled trials are difficult to perform. The quality of care can be determined primarily in the context of health care research using register studies. Registers enable standardized documentation of clinical observations over time. So far, no German register studies concerning DRFs exist, and therefore, the aim of this study was to develop a register with the help of patient-reported outcome measurements (PROM). Patients and Methods: All patients treated surgically at our hospital with a DRF between 2006 and 2016 were enrolled. Patient data such as epidemiological data, treatment, complications, insurance status, etc. were collected and the register was built up as an in-house fracture register with the help of PROM. The Munich Wrist Questionnaire (MWQ) was used as a PROM tool. Results: Of all 1.796 patients, 339 (19%) with a complete data set could be enrolled, 96 of the patients were male (28%), 243 were female (72%). 32% were type A (n=110), 9% (n=31) were type B and 58% (n=198) were type C fractures. The average follow-up was 66±31 months. Complications occurred in 25 cases (7%). The average postoperative function measured with the MWQ was 91±11%. Patients suffering from a DRF type A had the best outcome. It was significantly better than the outcome of patients with a DRF type C (95±7% vs. 89±13%, p<0.05 MWUT) and significantly better compared to the results from the whole fracture register (95±7% vs. 91±11%, p<0.05 MWUT). Type B fractures had a better outcome than type C fractures (92±11%). Conclusions: Retrospective register studies created with the help of PROM have numerous advantages. Data collection is fast, easy and cost-effective and a huge amount of data can be achieved from numerous patients and the observation period after surgery is quite long. The drop-out rate might be high, but patients enrolled are a representative sample compared to the current literature. This is a valuable tool for monitoring of clinical treatment quality.